Apoptosis in the kidneys of rats that experienced intrauterine growth restriction. (January 2015) - He, Xiaori; Xie, Zongde; Dong, Qingyi; Chen, Pingyang; Hu, Jingtao; Wang, Tao
Abstract Aim Intrauterine growth retardation (IUGR) can affect kidney development, leading to reduction in glomerular number. However, the associated cellular and molecular mechanisms have not been fully elucidated. This study investigated cell apoptosis and Bcl‐2 and Bax expression in the kidney of IUGR pups. Methods The IUGR model was established in pregnant rats with 10% low‐protein diet. Renal cell apoptosis was detected using TUNEL staining. Ki67 protein expression was measured by immunohistochemistry. Bcl‐2 and Bax mRNA expression was measured by real‐time polymerase chain reaction (PCR). Results Significant decreases in the number of glomeruli was observed in the kidney of IUGR pups 2 and 3 months after birth (P < 0.01). Obvious apoptosis was observed in the kidney in both groups 1 d, 7 d, and 21 d after birth with a peak at 7 d. Significantly higher apoptosis index was observed in the kidney of IUGR pups compared to control pups (P < 0.01). No significant difference in proliferation was observed between the two groups. Significantly lower Bcl‐2 mRNA expression, Bcl‐2/Bax ratio, and higher Bax mRNA expression were observed in IUGR pups compared to control pups after birth (P < 0.01). Conclusion The reduction in glomerular number in IUGR pups is associated with increase in renal cell apoptosis. The reduction in Bcl‐2/Bax ratio may play a crucial role in renal cell apoptosis in IUGR pups.